EFFECTS OF PERCEIVED PHYSICAL APPEARANCE SIMILARITY AND CONTROLLABILITY ON PERCEIVED ANTHROPOMORPHISM, TRUST, AND ACCEPTANCE TOWARDS ROBOTS - วรเมธพาสุข กฤตภัค; อิศรานนท์ หยกฟ้า (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2021)
This research aimed to investigate the effect of perceived anthropomorphism toward trust and acceptance in robots based on S-E-E-K theory; physical appearance similarity as independent variable, perceived of controllability as moderator and social motivation as controlled variable. Sample of 200 undergraduate and postgraduate students, aged between 18-25 years old were systematic and simple randomly assigned to one out of four conditions which were manipulated by a picture and a short description of the robot. The robots of each condition were designed to have different appearance (humanlike and not humanlike) and also behavior (predicted/controlled and not predicted/controlled). Afterward, participants completed the perceived anthropomorphism, trust in robot, acceptance in robot questionnaires. Results from Paths analysis showed that physical appearance similarity had relationship with a statistically significant on anthropomorphism. The effect of physical appearance similarity increased in the condition of unpredicted and uncontrollable robot. Furthermore, robot with highly humanlike appearance with unpredicted and uncontrolled behavior had the effect on participants’ feeling and it also increased trust and acceptance toward robots